Análise de tendência dos indicadores de monitoramento e avaliação da qualidade dos serviços de hanseníase em município prioritário do Nordeste brasileiro (Brazilian Journal of Health Research, 2018)
Trend analysis of leprosy indicators and evaluation of health services in a Northeastern Brazilian town seriously affected by leprosy